2008
DOI: 10.1007/s10552-008-9138-5
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma risk after exposure to fertility drugs: results from a large Danish cohort study

Abstract: Our findings showed no strong association between malignant melanoma risk and use of fertility drugs, although the results indicated that use of gonadotrophins or GnRH might increase risk in parous women. Longer follow-up is needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…This explanation seems less plausible than an explanation based on hormonal factors [44]. It is also possible that this is simply a chance finding, although one other group [21] found that exposure to fertility drugs commonly used in IVF (follicle-stimulating hormone, human menopausal gonadotropin and gonadotropin-releasing hormone) was associated with a two-to three-fold increase in the risk of melanoma in parous but not nulliparous women.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This explanation seems less plausible than an explanation based on hormonal factors [44]. It is also possible that this is simply a chance finding, although one other group [21] found that exposure to fertility drugs commonly used in IVF (follicle-stimulating hormone, human menopausal gonadotropin and gonadotropin-releasing hormone) was associated with a two-to three-fold increase in the risk of melanoma in parous but not nulliparous women.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies [17][18][19][20][21][22][23][24][25][26] have examined the association between fertility drug use and melanoma. Most had only small numbers of melanoma cases and most found no association between the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Briefly, the cohort comprised women with infertility referred to all Danish hospitals or private infertility clinics during 1963-98. In addition we included all women with a diagnosis of infertility (codes 628 and DN97, international classification of diseases, eighth and 10th revisions, respectively) recorded in the national patient registry, a nationwide register of virtually all discharges for somatic conditions from Danish hospitals since 1977.…”
Section: Methodsmentioning
confidence: 99%
“…49 Ovarian cancer in infertile women vs general population: SIR: 1.09; 95% CI: 0.30-1.60) Ovarian cancer in women exposed to fertility meds vs general population: SIR: 0.68; 95% CI: 0.01-3.80 [25] Venn et al (1995) Cohort of infertile women 1978-1992;…”
Section: Infertile Womenmentioning
confidence: 99%